Determinasi Minat Beli Ulang Produk Skincare Avoskin: Perspektif Influencer, Citra Merek Dan Kepercayaan Merek - Yuniawaty, Yunni; Istichanah, Istichanah (Soratekno Publisher, 2024)
In the current digital era, the beauty industry is experiencing rapid growth. Increasingly fierce competition encourages companies to implement various innovative marketing strategies. One popular strategy is to utilize the influence of influencers to promote products. Apart from that, brand image and consumer trust are also important factors that can influence purchasing decisions. This research aims to determine and analyze the influence of influencers, brand image and brand trust partially and simultaneously on interest in repurchasing Avoskin skincare products. The analysis method in this research is to use primary data taken from distributing questionnaires to 90 respondents who are students at Gunadarma University, Faculty of Economics, Management Study Program Class of 2024 who have purchased Avoskin skincare products at least once. The data collection method used was an online questionnaire via Google Form. The analytical tools used are data instrument tests, normality tests, classical assumption tests, multiple linear regression tests, hypothesis tests and coefficient of determination (R2) tests using the SPSS application. The research results show that the influencer variable partially has no effect on interest in repurchasing Avoskin skincare products. Meanwhile, brand image and brand trust variables partially influence interest in repurchasing Avoskin skincare products. Influencer variables, brand image and brand trust simultaneously influence interest in repurchasing Avoskin skincare products.